Current Proteomic and Metabolomic Knowledge of Zygotic and Somatic Embryogenesis in Plants - Juarez-Escobar, Janet; Bojórquez-Velázquez, Esaú; Elizalde-Contreras, Jose M.; Guerrero-Analco, José A.; Loyola-Vargas, Víctor M.; Mata-Rosas, Martín; Ruiz-May, Eliel (International journal of molecular sciences, 2021)
Embryogenesis is the primary developmental program in plants. The mechanisms that underlie the regulation of embryogenesis are an essential research subject given its potential contribution to mass in vitro propagation of profitable plant species. Somatic embryogenesis (SE) refers to the use of in vitro techniques to mimic the sexual reproduction program known as zygotic embryogenesis (ZE). In this review, we synthesize the current state of research on proteomic and metabolomic studies of SE and ZE in angiosperms (monocots and dicots) and gymnosperms. The most striking finding was the small number of studies addressing ZE. Meanwhile, the research effort focused on SE has been substantial but disjointed. Together, these research gaps may explain why the embryogenic induction stage and the maturation of the somatic embryo continue to be bottlenecks for efficient and large-scale regeneration of plants. Comprehensive and integrative studies of both SE and ZE are needed to provide the molecular foundation of plant embryogenesis, information which is needed to rationally guide experimental strategies to solve SE drawbacks in each species.